Developing a Working Model for Legal NGOs in China - Mei Qi (Washington University Global Studies Law Review, 2011)
The Article presents information related to non-governmental organizations (NGOs) in China and the civil societies. It further discusses the limitations of the NGOs due to Communist Party of China, the model proposed by the Beijing Children's Legal Aid and Research Center (BCLARC) and strategies for the proper implementation of the model. It also discusses the recent developments in government policies and civil society.
Keywords: Nongovernmental organizations; Civil society; Entail; Government policy; Legal aid; Zhongguo gong chan dang